Controlled Fabrication of Micropatterned Supramolecular Gels by Directed Self‐Assembly of Small Molecular Gelators. Issue 8 (30th January 2019) - Wang, Yiming; Oldenhof, Sander; Versluis, Frank; Shah, Maulik; Zhang, Kai; van Steijn, Volkert; Guo, Xuhong; Eelkema, Rienk; van Esch, Jan H.
Abstract: Herein, the micropatterning of supramolecular gels with oriented growth direction and controllable spatial dimensions by directing the self‐assembly of small molecular gelators is reported. This process is associated with an acid‐catalyzed formation of gelators from two soluble precursor molecules. To control the localized formation and self‐assembly of gelators, micropatterned poly(acrylic acid) (PAA) brushes are employed to create a local and controllable acidic environment. The results show that the gel formation can be well confined in the catalytic surface plane with dimensions ranging from micro‐ to centimeter. Furthermore, the gels show a preferential growth along the normal direction of the catalytic surface, and the thickness of the resultant gel patterns can be easily controlled by tuning the grafting density of PAA brushes. This work shows an effective "bottom‐up" strategy toward control over the spatial organization of materials and is expected to find promising applications in, e.g., microelectronics, tissue engineering, and biomedicine. Abstract : Controlled micropatterning of supramolecular gels is achieved by localized catalysis formation and self‐assembly of molecular gelators using catalytic polymer brush templates. Gels are locally formed and grow along the normal direction of the catalytic surface. The shapes and spatial dimensions of the resulting gel patterns can be precisely controlled by simply tuning the parameters of the brush templates.